A Constitutional Economics Perspective on Soft Paternalism. (25th January 2016) - Schnellenbach, Jan
Summary: Using a framework that distinguishes short‐term consumer preferences, individual reflective preferences and political preferences, we discuss from a constitutional economics perspective whether individuals find it in their common constitutional interest to endow representatives and bureaucrats with the competence to impose soft paternalist policies. The focus is specifically on soft paternalist policies, because these often work with non‐transparent "nudges" that are considered as manipulative in some contributions to the literature. We show that those soft paternalist policies that are manipulative indeed collide with three criteria of consumer sovereignty, reflective sovereignty, and citizen sovereignty that can be argued to represent common constitutional interest of citizens. On the other hand, we argue that the set of paternalist policies that is deemed acceptable on the constitutional level is restricted to non‐manipulative instruments, and their application as government policies is limited to cases with stable and very homogenous preferences. However, we also argue that competitive markets are capable of supplying many mechanisms that allow individuals to cope with problems in their decision‐making processes on a private level.